Formal versus traditional institutions: evidence from Ghana. Issue 2 (23rd February 2017) - Myers, William M.; Fridy, Kevin S.
ABSTRACT: Citizens in Ghana have a host of options when it comes to local governance provision as a result of the government's decentralization policies. We undertake to explore and understand how Ghanaians navigate the constellation of local institutions, both formal and traditional, to solve an array of common problems. A four-constituency survey was administered during the summer of 2009 and asked respondents about their experiences interacting with four formal institutions and one traditional institution. We find that formal institutions are by and large working effectively and are enhanced by the presence of a traditional institution. We consider the implications of our results with respect to both democratization and decentralization.